The Development of STEAM-Based Augmented Reality (AR) Instructional Material Model to Enhance 21st-Century Assessment Competencies for Junior High School Students - Siti Khayroiyah; Dara Fitrah Dwi; Hidayat; Novita Friska (Yayasan Darussalam Bengkulu, 2026)
This study aims to develop and evaluate a STEAM-based Augmented Reality (AR) instructional material model for improving junior high school students' 21st-century skills in solid geometry learning. The study employed a modified Research and Development model adapted from Borg and Gall, consisting of preliminary study and needs analysis, product design, expert validation, revision, limited trial, and large-scale field testing. The participants were 75 eighth-grade students. Data were collected using expert validation sheets, student response questionnaires, and 21st-century skills tests covering critical thinking, creativity, collaboration, and communication. The data were analyzed using quantitative descriptive statistics, normalized gain (N-Gain), and an independent-sample t-test. The results showed that the developed model achieved a mean expert validation score of 4.49, indicating a very valid category. The limited trial involving 15 students produced an N-Gain score of 0.46, categorized as moderate. The large-scale trial showed that the experimental class using the AR-STEAM model improved from a pretest score of 63.2 to a posttest score of 86.7, with an N-Gain of 0.63, whereas the control class improved from 62.9 to 72.4, with an N-Gain of 0.26. The t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the experimental and control classes. These findings demonstrate that the AR-STEAM model is valid and effective for enhancing students' 21st-century skills through interactive three-dimensional visualization, project-based learning, contextual problem solving, and competency-oriented assessment.